ONLINE SCAM: A SYSTEMATIC LITERATURE REVIEW - Jais, Zurairah; Shahrul Azmi, Salbiah Nur; Mohd Hasini, Noor Fariza; Samsudin, Shahrul Niza; Izhar, Nor Izzuani; Idris, Nor Ainee; Abu Hassan, Azwan Amirulsyafiq (Jurnal 'Ulwan, 2024)
The rise in crime involving online scam is increasing each year. A total of 107, 716 cases involving losses amounting to RM 3.2 billion were detected by the National Security Council from 2020 to 2023. Although various parties such as the Royal Malaysia Police (PDRM) in collaboration with the government and government agencies have made announcements on the modus operandi of online scam, it is still not fully effective. In Malaysia, there is the lack of studies on online scam although the statistics of cases reported are increasing from year to year. Thus, this study characterizes the literary landscape related to online scam crime to provide a deep understanding as well as identify the frequency of studies by systematically reviewing the previous studies through PRISMA method. This paper provides a literature review on online scam crime to provide a deep understanding on the issues. Additionally, this paper identifies the frequency of studies by systematically reviewing the previous studies through PRISMA method. Ultimately, the implication of this study from the academic aspect are to identify the adaptation of the KAP model, study appropriate research methods and the frequency of research related to online scam in Malaysia.